Pengaruh Estimasi Arus Kas, Biaya Modal, dan Risiko Proyek terhadap Kelayakan Investasi pada Perusahaan Manufaktur yang Terdaftar di BEI (Jurnal Ekonomi Bisnis dan Akuntansi, 2025)
This research intends to analyze the influence of estimated cash flow, capital costs, and project risks on the feasibility of investment in public companies (Tbk) on the Indonesia Stock Exchange (IDX). Data was taken from 50 Tbk companies for the 2022–2024 period. The analysis involved the use of multiple linear regression modeling, after ensuring the fulfillment of the assumptions of normality, multicollinearity, and homogeneity. The findings revealed that the estimated cash flow had a positive and significant effect on the feasibility of the investment, while the cost of capital and project risk had no significant effect. These findings emphasize the importance of accurate cash estimates in investment decision-making.